Socio-demographic profile and treatment outcomes in pediatric TB patients attending DOTS centers in urban areas of Delhi - Dhaked, S.; Sharma, N.; Chopra, K.K.; Khanna, A.; Kumar, R. (Indian journal of tuberculosis, 2019)
India accounts for one fourth of the global tuberculosis (TB) burden. In 2015, an estimated 28 lakh cases occurred and 4.8 lakh people died due to TB and proportion of children among new TB patients was 6% in 2016. The clinical presentation of childhood TB is extremely variable, therefore the study attempted to understand, the socio-demographic profile of pediatric tuberculosis patients, and the treatment outcomes under Revised National Tuberculosis Control Program (RNTCP). It was a prospective study carried out from January 2015 to December 2015. A predesigned, pretested and semi-structured questionnaire was used to interview caregivers of pediatric TB patients and they were followed up at two more occasions i.e. at the end of intensive phase at the end of continuation phase. A total of 141 study subjects were enrolled. Majority of the subjects (51.8%) belonged to 11–14 years of age group were females (63.8%) and from lower middle class families (48.9%). Extra pulmonary TB (70.2%) was almost three times more prevalent than pulmonary TB. During follow up visits symptoms like chest pain, breathlessness and eye redness were disappeared by the end of intensive phase and fever, cough and skin lesion improved by the end of continuation phase. Mean weight gain in malnourished children (2.6 kg) was lesser as compared to normal children (3.0 kg) at the end of 3rd visit. Treatment success rate in category 1 was 96.2% and in category 2 was 90%. Treatment success rate under RNTCP is good but still need to improve, to make it 100 percent.